Detection of Enterobacteriaceae producing Extended Spectrum -Lactamases (ESBL) in Beef Cattle Sold at the Animal Market in Central Lombok - Dian Neni Naelasari; Febrina Sulistiawati (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The Province of West Nusa Tenggara Province (NTB) is known as a source of beef cattle in eastern Indonesia. The use of antibiotics in animal foods can threaten health and cause antibiotic resistance to the normal flora of the animal and humans. One of the causes of antibiotic resistance is extended spectrum β-lactamase (ESBL). The purpose of the study was to detect the prevalence of ESBL-producing Enterobacteriaceae in beef cattle sold in the central Lombok animal market. The faecal samples were collected from beef cattle to 65. Cultured on MacConkey agar supplemented with cefotaxim 1 mg/L, incubated at 37oC for 24 hours. Then the growing colony were tested for ESBL producer by Double Disk Synergy Test (DDST). Identify the type of bacteria by biochemical testing. Identify the type of bacteria by biochemical testing and gram staining. Results: identified showed 1 (1.5%) sample of ESBL positive beef cattle the faecal samples with Escherichia coli bacteria (100%). Through feces, resistant bacteria contained in animal faecal can migrate to the environment and cross-transmission of genetic material between bacteria through water, soil, air, plants, food, humans and food-producing animals.